Carbon-based self-cleaning membrane material for efficiently separating oil-water emulsion as well as preparation method and application of carbon-based self-cleaning membrane material

By combining carbon nanotubes with Cu-ZnIn2S4 photocatalytic material, CNTs-PEI/CZIS composite film was prepared, which solved the problems of oil-adhesive scaling and adsorption materials in the existing film materials, and achieved efficient separation of oil-water emulsions and self-cleaning effects. .

CN119281143AActive Publication Date: 2025-01-10ZHEJIANG UNIV OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411813739.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-01-10
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Existing membrane materials are prone to sticking to oil and fouling during oil-water separation, resulting in clogging of membrane pores, reducing separation efficiency, increasing energy consumption, and difficult to recover after saturation of adsorbent materials, which easily leads to secondary pollution and makes it difficult to effectively treat emulsified oil.

Method used

Using carbon-based self-cleaning membrane material, CNTs-PEI was prepared by combining carbon nanotubes with Cu-ZnIn2S4 photocatalytic material, photocatalytic degradation of oil stains on the surface of the membrane and enhancing anti-fouling properties. The polymer functionalization and vacuum-assisted filtration method were used to prepare CNTs-PEI. /CZIS composite membrane has excellent hydrophilicity and self-cleaning ability.

Benefits of technology

It has achieved efficient separation of oil and water emulsions, with a separation efficiency of up to 99.6%. The residual oil and soil are degraded by photocatalytic, which enhances the anti-fouling performance of the film, and the material is stable and recyclable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281143A_ABST
    Figure CN119281143A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsion as well as a preparation method and application of the carbon-based self-cleaning membrane material. The preparation method of the carbon-based self-cleaning membrane material comprises the following steps: functionalizing acidified carbon nanotubes (CNTs) through polyethyleneimine (PEI) to obtain a CNTs-PEI material; filtering the CNTs-PEI dispersoid onto a polyvinylidene fluoride (PVDF) membrane by adopting a vacuum-assisted filtering method, so as to obtain a CNTs-PEI membrane; and filtering the Cu-ZnIn2S4 dispersoid on the CNTs-PEI membrane, so as to obtain the carbon-based self-cleaning membrane material CNTs-PEI / CZIS for efficiently separating the oil-water emulsion. The separation efficiency of the CNTs-PEI / CZIS membrane material to chloroform / water emulsion can reach 99.6 + / -0.4%, and the CNTs-PEI / CZIS membrane material has good broad-spectrum applicability, chemical adaptability and stability, and is a promising composite functional membrane material capable of cyclically and efficiently separating oil-water emulsion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of composite membrane materials for oil-water separation, and specifically relates to a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions, and a preparation method and application thereof. Background Art

[0002] The harmless treatment and resource utilization of oily wastewater from petroleum, petrochemical, kitchen, etc. is an important guarantee for water environmental safety and sustainable industrial development. Traditional methods for treating oily wastewater include sedimentation, flotation, adsorption and filtration. Sedimentation and flotation are effective methods for separating oil-water mixtures, but it is difficult to treat emulsified oil. Adsorption separation usually uses porous materials such as sponges to adsorb and remove grease from wastewater, but these materials have a certain absorption rate and are difficult to recycle after saturation, which easily causes secondary pollution. The filtration separation method treats oily wastewater based on the principle of pore size screening. It separates by selecting filtration separation materials with different pore sizes. The current operation method is mainly membrane separation. Existing membrane materials, such as polyvinylidene fluoride and polyether sulfone, are prone to oil and scale on the membrane surface during oil-water separation, resulting in clogging of membrane pores, reduced separation efficiency and increased energy consumption. Therefore, it is urgent to develop new membrane materials with excellent oil-water separation efficiency and anti-pollution performance to achieve stable and efficient oil-water separation effects.

[0003] Since carbon nanotubes have a high specific surface area and mechanical strength, they are often used as separation membranes for modification. By introducing hydrophilic and hydrophobic groups, hydrophilic / underwater superoleophobic oil-water separation membranes are constructed. In addition, composite materials are one of the important development directions of functional materials. Photocatalytic materials can achieve photocatalytic degradation of pollutants under the drive of visible light irradiation under the appropriate band gap, and also have the advantages of stability, non-toxicity, and self-cleaning. Cu can be used as a platform for effective light-driven chemical reactions. By combining with the ternary sulfide ZnIn2S4 with excellent photocatalytic properties to form a synergistic effect, the catalytic performance is improved. Combining catalytic materials with membrane separation technology and using photocatalytic materials to degrade residual oil on the membrane surface is a powerful means to enhance the anti-fouling performance of membrane materials. Summary of the invention

[0004] In order to overcome the shortcomings and deficiencies in the prior art, the object of the present invention is to provide a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions, and a preparation method and application thereof.

[0005] In order to achieve the above objectives, the following technical solutions are proposed: A method for preparing a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions comprises the following steps: Step 1: Dissolve zinc salt, indium salt and sulfur source in ultrapure water, adjust the pH value of the mixed solution to acidic, transfer the mixed solution to a hydrothermal reactor, seal the hydrothermal reactor and place it in an oven for reaction. After the reaction is completed, wait for the reactor to cool to room temperature, centrifuge, wash and dry the precipitate to obtain the sulfur-indium-zinc composite material ZnIn2S4. Ultrasonic disperse the sulfur-indium-zinc composite material ZnIn2S4 in ultrapure water and mix it with a copper salt solution; slowly inject a reducing solution under magnetic stirring and light irradiation, and perform a photodeposition reaction for 5-180 min to obtain Cu-ZnIn2S4.

[0006] Step 2: The carbon nanotubes CNTs are subjected to heating and acidification treatment in a mixed solution of concentrated H2SO4 / concentrated HNO3, and then the supernatant is removed by standing. The lower layer product is washed with distilled water until it is neutral and dried to obtain acidified carbon nanotubes CNTs-COOH.

[0007] Step 3: The acidified carbon nanotubes CNTs-COOH obtained in step 2 are ultrasonically dispersed in water together with polyethyleneimine PEI, and then centrifuged, washed, and dried in sequence to obtain PEI-functionalized CNTs, which are recorded as CNTs-PEI.

[0008] Step 4: Disperse the CNTs-PEI obtained in step 3 with water to obtain a dispersion, and filter the dispersion onto a hydrophilic polyvinylidene fluoride (PVDF) membrane to obtain a CNTs-PEI membrane.

[0009] Step 5: Disperse Cu-ZnIn2S4 with water to obtain a dispersion, and filter the dispersion onto the CNTs-PEI membrane obtained in step 4 to obtain a CNTs-PEI / Cu-ZnIn2S4 composite membrane, and the preparation is completed.

[0010] Furthermore, the zinc salt in step 1 is zinc nitrate, zinc sulfate, zinc chloride, zinc phosphate, zinc acetate, zinc citrate, zinc isooctanoate or zinc glycinate, the indium salt is indium nitrate, indium sulfate, indium chloride, indium phosphate, indium acetate or indium citrate, and the sulfur source is thioacetamide, thiourea, ammonium sulfide or sodium thiosulfate. The molar ratio of the zinc salt, indium salt and sulfur source is 2-3:4-6:8-12.

[0011] Furthermore, the copper salt in step 1 is copper nitrate, copper chloride, copper phosphate, copper acetate or sodium copper ethylenediaminetetraacetate, and the mass ratio of the copper salt to the indium zinc sulfide material is 0.1-2:10.

[0012] Furthermore, the reducing solution in step 1 is hydrazine, sodium borohydride, potassium borohydride, ethanol, ammonia water or sodium sulfite, the concentration of the reducing solution is 0.01-0.6 mol / L, the molar ratio with the copper salt is 3-15:1, and the injection speed of the reducing solution is 2-3 drops per second.

[0013] Furthermore, in step 2, during the heating and acidification of carbon nanotubes CNTs, the volume ratio of concentrated H2SO4 solution to concentrated HNO3 solution is 1-4:1, preferably 2-3:1, the mass fraction of concentrated H2SO4 solution is 95-98%, and the mass fraction of concentrated HNO3 solution is 65-70%; the temperature of the heating and acidification treatment is 60-80°C, and the time is 0.5-2 h.

[0014] In step 2 of the present invention, the acidified CNTs are functionalized with PEI, so that the surface of CNTs-PEI contains hydrophilic amino groups and carboxyl groups, and has a higher affinity for water.

[0015] Furthermore, in step 3, the dispersion concentrations of the acidified carbon nanotubes CNTs-COOH and polyethyleneimine PEI in water are 0.05-0.2 g / L and 0.5-2 g / L, respectively, preferably 0.08-0.12 g / L and 0.8-1.2 g / L, respectively; and the ultrasonic dispersion time in step 3 is 0.5-2 h.

[0016] Further, in step 4, under the condition of 0.9 bar (90 kPa), a vacuum-assisted filtration method is used to deposit the carbon nanotubes on a hydrophilic polyvinylidene fluoride (PVDF) membrane to form a thin film.

[0017] The present invention also discloses the application of the carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions in membrane separation of oil-water emulsions. After the membrane separation is completed, the following regeneration treatment step is also included: after washing 2-4 times with alcohol and water alternately to remove part of the oil component, the membrane is irradiated with visible light.

[0018] The CNTs-PEI / CZIS composite membrane of the present invention has excellent hydrophilicity and oleophobicity, making it a promising membrane separation material for efficient separation of oil-water emulsions. Taking chloroform / water (C / W) emulsion as an example, the separation flux of the CNTs-PEI / CZIS composite membrane is (2070 ± 19 L m -2 h -1 bar -1 ), the separation efficiency can reach 99.6 ± 0.4%.

[0019] The hydrophilic functional groups (-COOH, -NH2) imparted by PEI functionalization in the present invention can effectively prevent oil from adhering to the inner / outer surface of the membrane. The excellent photocatalytic performance of Cu-ZnIn2S4 can catalyze the degradation of residual oil components and other impurities. The two complement each other to enable the CNTs-PEI / CZIS composite membrane to have extremely strong self-cleaning ability.

[0020] The beneficial effects of the present invention are: 1) A series of CNTs-PEI / CZIS composite membranes were designed and prepared by polymer functionalization and vacuum-assisted filtration. By acidifying carbon nanotubes and functionalizing them with polyethyleneimine, they were endowed with abundant hydrophilic functional groups, making the CNTs-PEI / CZIS composite membranes have excellent hydrophilic and oleophobic properties and special wettability, effectively preventing oil from adhering to the inner / outer surfaces of the membrane. The excellent photocatalytic properties of Cu-ZnIn2S4 can catalytically degrade the residual oil components and other impurities on the membrane, effectively enhancing the anti-fouling performance of the membrane material.

[0021] 2) Taking chloroform / water (C / W) emulsion as an example, the separation flux of CNTs-PEI / CZIS composite membrane is (2070 ± 19 L m -2 h -1 bar -1 ), the separation efficiency can reach 99.6 ± 0.4%. Through the circulation experiment and the anti-fouling performance experiment of different emulsions, it is further shown that CNTs-PEI / CZIS has good chemical adaptability, high stability of the composite membrane, recyclability, self-cleaning and wide applicability, and is a promising composite functional membrane material that can efficiently separate oil-water emulsions. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD spectra of CNTs-PEI, CNTs-PEI / ZIS and CNTs-PEI / CZIS composite film materials prepared in Example 1; Figure 2 EDS element distribution diagram of Cu-ZnIn2S4 prepared in Example 1; Figure 3 This is a comparison chart of separation flux and separation efficiency of the composite membrane materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 for chloroform / water (C / W); Figure 4 This is a comparison diagram of the water flux of the CNTs-PEI / CZIS composite membrane material prepared in Example 1 before and after separation of chloroform / water (C / W) emulsion; Figure 5 This is a diagram showing the recycling effect of the CNTs-PEI / CZIS composite membrane material prepared in Example 1; Figure 6 This is a diagram showing the effect of the CNTs-PEI / CZIS composite membrane material prepared in Example 1 on separating different oil-in-water emulsions. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with the embodiments and the accompanying drawings, but the protection scope of the present invention is not limited thereto.

[0024] Example 1 Preparation of CNTs-PEI / CZIS composite membrane material;

[0025] Preparation of CNTs-PEI / CZIS self-cleaning membrane materials: 1) Carbon nanotubes (CNTs, purity > 95%, ID: 5-10 nm, OD: 10-20 nm, Length: 10-30 nm, purchased from MacLean Reagent Co., Ltd.) were heated at 70 °C for 2 h in a mixed solution of 95-98% H2SO4 and 70% HNO3 in a volume ratio of 3:1; after the heating, the solution was allowed to stand and the supernatant was removed, distilled water was added to the lower solution, and the solution was allowed to stand and stratified, and the above steps were repeated 3 times or more until it became neutral; the obtained neutral solution was filtered and washed to remove impurities; the black substance obtained by filtration was placed in a vacuum drying oven at 40 °C and dried overnight to obtain acidified carbon nanotubes, recorded as CNTs-COOH; 2) Disperse 0.02 g of acidified carbon nanotubes (CNTs-COOH) and 0.2 g of polyethyleneimine (PEI, molecular weight 43.04, purity 50%, purchased from Roen Reagent Co., Ltd.) in 200 mL of ultrapure water and disperse by ultrasonic for 1 h; centrifuge the mixed solution at 8000 r / min for 10 min, remove the supernatant, wash the precipitate with ultrapure water for 3 to 5 times, and dry it at 30 °C to obtain PEI-functionalized CNTs, which are recorded as CNTs-PEI; 3) Prepare CNTs-PEI dispersion with 100 mg / L of CNTs-PEI using water solvent; 10 mL of the dispersion was filtered at 0.9 bar (90 kPa) to an effective area of ​​40 cm 2 On a polyvinylidene fluoride membrane (PVDF, pore size 0.45 μm, purchased from Shanghai Titan Technology Co., Ltd.), a 40 cm 2 CNTs-PEI membrane; 4) Cu-ZnIn2S4 is referred to as CZIS. Use water solvent to prepare a 100 mg / L Cu-ZnIn2S4 dispersion for later use. 2 25 mL of Cu-ZnIn2S4 dispersion was filtered on the CNTs-PEI membrane to obtain the CNTs-PEI / CZIS composite membrane.

[0026] 5) ZnIn2S4 material is referred to as ZIS. The ZnIn2S4 material is prepared into a 100 mg / L ZnIn2S4 dispersion using water solvent and set aside. The 40 cm 2 25 mL of ZnIn2S4 dispersion was filtered on the CNTs-PEI membrane to obtain the CNTs-PEI / ZIS composite membrane.

[0027] Preparation of the above-mentioned ZnIn2S4 material: 0.068 g ZnCl2, 0.239 g InCl2·4H2O and 0.15 g CH3CSNH2 were dissolved in 40 mL ultrapure water and magnetically stirred for 30 min to form a mixed metal salt solution; the mixed solution was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner; the hydrothermal reactor was sealed and placed in an oven and kept warm at 160°C for 16 h; after the reaction was completed, the precipitate was cooled to room temperature, centrifuged and washed several times with ultrapure water and anhydrous ethanol to obtain a dark yellow solid substance, which was placed in a vacuum oven at 60°C for vacuum drying for 12 h to obtain the ZnIn2S4 material.

[0028] Preparation of the above-mentioned Cu-ZnIn2S4 material: 4.2 mg CuCl2 was ultrasonically dissolved in 5 mL ultrapure water to prepare a copper ion solution for use; 14.3 mg NaBH4 was ultrasonically dissolved in 5 mL ultrapure water to prepare a sodium borohydride aqueous solution for use; 100 mg of the prepared ZnIn2S4 material was ultrasonically dispersed in 40 mL of water, mixed with the prepared copper ion solution, and moved into a quartz photoreactor after ultrasound, nitrogen bubbling was used to remove dissolved oxygen, a 300 W xenon lamp was used as the experimental light source, and under magnetic stirring, the sodium borohydride aqueous solution was injected at a rate of 2 drops per second. After the addition was completed, the reaction was continued for 60 minutes to complete the photodeposition reaction, and room temperature was maintained in a constant temperature water bath during the period; after the reaction was completed, ultrapure water and anhydrous ethanol were used for centrifugal washing to remove residual salt, and dried in a vacuum oven at 60°C for 12 hours to obtain Cu-ZnIn2S4 material.

[0029] The XRD spectra of the CNTs-PEI film, CNTs-PEI / ZIS composite film and CNTs-PEI / CZIS composite film prepared in Example 1 are as follows: Figure 1 As shown in the figure, the prepared CNTs-PEI material has obvious standard diffraction peaks of carbon-based materials, corresponding to the (002) and (110) crystal planes of carbon materials. In the XRD spectra of CNTs-PEI / ZIS and CNTs-PEI / CZIS composite films, the characteristic diffraction peaks of ZIS can be clearly observed, corresponding to the (006), (102), (110) and (116) crystal planes of hexagonal ZIS (JCPDS No. 72-0773), indicating that CZIS and CNTs-PEI have been successfully composited. In the XRD spectrum of CNTs-PEI / CZIS composite film, the characteristic diffraction peaks of Cu are not obvious due to the low loading amount.

[0030] The EDS element distribution diagram corresponding to Cu-ZnIn2S4 is shown in Figure 2As shown, the Zn, In, S, and Cu elements of the material are evenly distributed, which indicates that the in-situ photochemical deposition method can make Cu evenly distributed on the ZIS.

[0031] Example 2 Emulsion separation performance of CNTs-PEI / CZIS composite membrane material

[0032] The separation performance of the membrane material was evaluated by preparing different types of oil / water (O / W) emulsions and calculating the permeation flux and separation efficiency of the emulsions. The emulsion preparation steps were as follows: 0.8 g of emulsifier Tween-80 (sorbitan monooleate polyoxyethylene ether) and 4 mL of oil (the oil was selected from chloroform, dichloromethane, hexane, toluene, silicone oil or soybean oil) were added to 120 mL of water and stirred vigorously for 8 h to obtain chloroform / water (C / W) emulsion, dichloromethane / water (D / W) emulsion, n-hexane / water (H / W) emulsion, toluene / water (T / W) emulsion, silicone oil / water (Si / W) emulsion, and soybean oil / water (So / W) emulsion, respectively.

[0033] Permeation flux ( J ) is an important indicator for evaluating the separation performance of composite membranes. The larger the permeation flux, the faster the water molecules pass through the membrane; the smaller the permeation flux, the slower the diffusion of water molecules from outside the membrane to inside the membrane. The calculation formula is as follows: ; In the formula, ——Infiltration water volume, L; A——effective membrane area, m 2 ; ——operation time, h; ——Transmembrane pressure difference, bar.

[0034] In the process of membrane separation, different solute molecules have different permeability. The oil concentration in the liquid before and after filtration is measured by TOC, and the separation efficiency of the membrane material for the emulsion is calculated. R (%), the formula is as follows: ; Where, C0——Oil concentration of initial emulsion, mg / L; C f ——Oil concentration in the filtrate, mg / L.

[0035] Taking chloroform / water (C / W) emulsion as an example, when the filtration pressure is 0.3 bar, the permeate flux and separation efficiency of the emulsion are calculated by measuring the permeate volume of 50 mL of emulsion separated within 30 minutes and the oil concentration in the liquid before and after filtration. According to the test conditions, the separation flux and efficiency of the CNTs-PEI membrane, CNTs-PEI / ZIS composite membrane and CNTs-PEI / CZIS composite membrane prepared in Example 1 for chloroform / water (C / W) separation for 30 minutes are as follows: Figure 3 As shown (separation flux is a bar graph, separation efficiency is a dotted line graph).

[0036] from Figure 3 It can be seen that the CNTs-PEI membrane has a higher separation flux for C / W emulsion (2150 ± 69 L m -2 h -1 bar -1 ), the separation efficiency was 92.4 ± 0.3%. After modification with ZIS or CZIS, the pores of CNTs-PEI / ZIS composite membrane and CNTs-PEI / CZIS composite membrane were slightly affected, and the separation flux decreased slightly, but the separation efficiency increased to 98.5 ± 0.7% and 99.6 ± 0.4%, respectively. In addition, due to the modification of CuNPs on the ZIS surface, it provided more specific surface area and active sites than pure ZIS, and the separation flux of CNTs-PEI / CZIS composite membrane (2070 ± 19 L m -2 h -1 bar -1 ) was higher than that of CNTs-PEI / ZIS composite membrane (1920 ± 100 L m -2 h -1 bar -1 ).

[0037] Comparative Example 1 Preparation of CNTs*-PEI composite membrane material

[0038] 0.02 g carbon nanotubes (CNTs) and 0.2 g polyethyleneimine (PEI) were dissolved in 200 mL ultrapure water and ultrasonically dispersed for 1 h. The mixed solution was centrifuged at 8000 r / min for 10 min, the supernatant was removed, the precipitate was washed with ultrapure water for 3-5 times, and dried at 30 °C to obtain PEI-functionalized CNTs, which was recorded as CNTs*-PEI. CNTs*-PEI was prepared into a 100 mg / L CNTs*-PEI dispersion. 10 mL of the dispersion was filtered at 0.9 bar (90 kPa) to an effective area of ​​40 cm by vacuum assisted filtration. 2 CNTs*-PEI membrane was obtained on polyvinylidene fluoride (PVDF) membrane.

[0039] Comparative Example 2 Preparation of CNTs-PAA / CZIS composite film material

[0040] 1) 0.15 g of carbon nanotubes were ultrasonically dispersed in 150 mL of acetone, and 3.0 g of acrylic acid (AA) and 0.065 g of recrystallized benzoyl peroxide (BPO) were added, and stirred at 75 °C for 8 h under N2 atmosphere. The obtained CNTs-PAA was collected by filtration, washed with deionized water three times, and dried at 30 °C to obtain CNTs modified with hydrazide functional groups, which was recorded as CNTs-PAA; 2) Prepare CNTs-PAA into a 100 mg / L CNTs-PAA dispersion; filter 10 mL of the dispersion at 0.9 bar (90 kPa) to an effective area of ​​40 cm using vacuum-assisted filtration. 2 On polyvinylidene fluoride (PVDF) membrane, CNTs-PAA membrane was obtained; 3) Cu-ZnIn2S4 is referred to as CZIS. Use water solvent to prepare a 100 mg / L Cu-ZnIn2S4 dispersion for later use. 2 25 mL of Cu-ZnIn2S4 dispersion was filtered on the CNTs-PAA membrane to obtain the CNTs-PAA / CZIS composite membrane.

[0041] 4) ZnIn2S4 material is referred to as ZIS. The ZnIn2S4 material is prepared into a 100 mg / L ZnIn2S4 dispersion using water solvent and set aside. The 40 cm 2 25 mL of ZnIn2S4 dispersion was filtered on the CNTs-PAA membrane to obtain the CNTs-PAA / ZIS composite membrane.

[0042] The preparation steps of Cu-ZnIn2S4 and ZnIn2S4 in Comparative Example 2 repeat those of Example 1.

[0043] Comparative Example 3 Emulsion separation performance of CNTs*-PEI and CNTs-PAA / CZIS composite membrane materials

[0044] Referring to the emulsion separation conditions in Example 2, chloroform / water (C / W) emulsion was selected as the separation object.

[0045] The separation flux and efficiency of the CNTs*-PEI membrane of Comparative Example 1, the CNTs-PAA membrane of Comparative Example 2, the CNTs-PAA / ZIS composite membrane and the CNTs-PAA / CZIS composite membrane for chloroform / water (C / W) separation for 30 min are shown in FIG. Figure 3As shown in Figure 2, the separation flux of CNTs*-PEI membrane for C / W emulsion was relatively low (1420 ± 53 L m -2 h -1 bar -1 ), the separation efficiency is 83.1 ± 0.2%, and the separation flux and separation efficiency are significantly lower than those of the CNTs-PEI membrane obtained by using acidified carbon nanotubes in Example 2, which indicates that the acidification treatment of carbon nanotubes can effectively improve the hydrophilicity of the carbon nanotube membrane material, thereby improving the separation performance of the membrane material.

[0046] The separation flux of CNTs-PAA membrane for C / W emulsion can reach (1840 ± 53 L m -2 h -1 bar -1 ), the separation efficiency was 91.2 ± 0.4%. After modification with ZIS or CZIS, the pores of CNTs-PAA / ZIS composite membranes and CNTs-PAA / CZIS composite membranes were slightly affected, and the separation flux decreased to 1600 ± 80 L m -2 h -1 bar -1 and 1740 ± 20 Lm -2 h -1 bar -1 , but the separation efficiency was improved to 95.3 ± 0.2% and 96.7 ± 0.5%, respectively. Similarly, since CuNPs were modified on the surface of ZIS, providing more abundant specific surface area and active sites than pure ZIS, the separation flux of CNTs-PAA / CZIS composite membrane was higher than that of CNTs-PAA / ZIS composite membrane.

[0047] By comparing the permeation flux and separation efficiency of the composite membranes for C / W emulsions, it can be seen that the separation performance of CNTs-PEI, CNTs-PEI / ZIS and CNTs-PEI / CZIS composite membranes is significantly better than that of CNTs-PAA, CNTs-PAA / ZIS and CNTs-PAA / CZIS composite membranes. This may be because the acidified CNTs are functionalized with PEI, so that the surface of CNTs-PEI contains hydrophilic amino and carboxyl groups, which has a higher affinity for water.

[0048] Example 3 Self-cleaning performance of CNTs-PEI / CZIS composite membrane material;

[0049] Referring to the emulsion separation conditions in Example 2, chloroform / water (C / W) emulsion was selected as the separation object, and the anti-fouling performance of the membrane material, i.e., the self-cleaning performance, was tested by calculating the water flux before and after the C / W emulsion separation, so as to evaluate the practical applicability and comprehensive performance of the membrane. The CNTs-PEI / CZIS composite membrane prepared in Example 1 was used for evaluation, and the initial / recovered water flux (initial, after emulsion separation, after water washing, after sunlight irradiation) during the C / W emulsion separation was as follows: Figure 4 As shown in Figure 2, the initial water flux of CNTs-PEI / CZIS composite membrane for pure water separation at 0.3 bar pressure for 30 min ( J 0 ) is 13090 ± 940 L m -2 h -1 bar -1 The obtained membrane was recorded as the initial membrane. The initial membrane was separated from chloroform / water (C / W) for 30 min at 0.3 bar pressure according to the emulsion separation conditions in Example 2. The water flux of the membrane was tested for separation of pure water for 30 min at 0.3 bar pressure ( J 1 ) as low as 2070 ± 19 L m -2 h -1 bar -1 , which can be attributed to the aggregation and adhesion of oil droplets in the emulsion on the surface and inside of the membrane, and the obtained membrane is recorded as the membrane after emulsion separation.

[0050] The membrane was regenerated for the first time after emulsion separation, washed with water / alcohol alternately for 3 times, dried at 30 °C, and then the water flux of the membrane was measured for pure water separation at a pressure of 0.3 bar for 30 min ( J 2 ) recovered to 5630 ± 370 L m -2 h -1 bar -1 , which indicates that water and alcohol cannot play a deep cleaning role, and the obtained membrane is recorded as the regenerated membrane after water washing.

[0051] The washed regenerated membrane was regenerated again, and the composite membrane was irradiated with a 300 W xenon lamp to simulate sunlight for 30 min, and then pure water was separated at a pressure of 0.3 bar for 30 min. The recovered water flux of the CNTs-PEI / CZIS composite membrane ( J 3 ) recovered to 13010 ± 830 L m -2 h -1 bar -1 This indicates that the film has good visible light absorption and self-cleaning ability.

[0052] Example 4 Stability of CNTs-PEI / CZIS composite membrane material

[0053] Referring to the emulsion separation conditions in Example 2, chloroform / water (C / W) emulsion was selected as the separation object, and the CNTs-PEI / CZIS composite membrane of Example 1 was used to perform multiple cycles of separation on the C / W emulsion. Each emulsion separation experiment was to continuously separate the chloroform / water (C / W) emulsion at a pressure of 0.3 bar for 60 min, and the separation data in two time periods of 0-30 min and 30-60 min were recorded, that is, two sets of experimental data were recorded for each emulsion separation experiment, and the corresponding separation flux and separation efficiency were calculated according to the formula in Example 2.

[0054] The membrane was regenerated after each emulsion separation experiment. The composite membrane was first washed three times with alcohol / water alternately, dried at 30 °C, and then irradiated with a 300 W xenon lamp to simulate sunlight for 30 min to obtain the regenerated composite membrane, which was then used for the next emulsion separation experiment.

[0055] According to the above experimental process, the experimental results of multiple cycles of separation of C / W emulsion by the CNTs-PEI / CZIS composite membrane of Example 1 are shown in Figure 5 The stability of the composite membrane was determined by the separation flux and separation efficiency of the composite membrane for multiple separations of C / W emulsions, thereby evaluating the practical application prospects of the CNTs-PEI / CZIS composite membrane. Figure 5 The recycling effect of CNTs-PEI / CZIS composite membrane can be seen in the figure (separation flux is a line graph, and separation efficiency is a dot graph). During multiple cycles, the separation efficiency of CNTs-PEI / CZIS composite membrane for C / W emulsion always remains at or above 95%, and the separation flux remains stable.

[0056] Example 5 Application performance evaluation of CNTs-PEI / CZIS composite membrane materials

[0057] Referring to the emulsion separation conditions in Example 2, in order to evaluate the actual performance of the CNTs-PEI / CZIS composite membrane prepared in Example 1, the separation performance tests were also carried out on other emulsions. The separation results of different water-in-oil emulsions are shown in FIG. Figure 6 As shown in the figure (separation flux is a bar graph, and separation efficiency is a dotted line graph), the separation fluxes of D / W emulsion, H / W emulsion, T / W emulsion, So / W emulsion, and Si / W emulsion are 2150 ± 69, 4880 ± 450, 6470 ± 500, 4130 ± 310, and 2380 ± 100 L m -2 h -1 bar -1, the separation efficiencies were 98.5 ± 0.5%, 96.4 ± 0.6%, 99.7 ± 0.3%, 97.6 ± 0.4% and 97.4 ± 0.6%, respectively. This indicates that the CNTs-PEI / CZIS composite membrane has good practical applicability and can separate a variety of emulsions with high separation efficiency, further illustrating its excellent hydrophilic and oleophobic properties.

Claims

1. A method for preparing a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions, characterized in that The following steps are involved: Step 1: The carbon nanotubes CNTs are heated and acidified in a mixed solution of concentrated H2SO4 / concentrated HNO3, and then the supernatant is removed by standing, and the lower layer product is washed with distilled water until it is neutral, and dried to obtain acidified carbon nanotubes CNTs-COOH; Step 2: The acidified carbon nanotubes CNTs-COOH obtained in step 1 are ultrasonically dispersed in water together with polyethyleneimine PEI, and then centrifuged, washed, and dried in sequence to obtain PEI-functionalized CNTs, which are recorded as CNTs-PEI; Step 3: dispersing the CNTs-PEI obtained in step 2 with water to obtain a dispersion, filtering the dispersion onto a hydrophilic polyvinylidene fluoride (PVDF) membrane to obtain a CNTs-PEI membrane; Step 4: Disperse Cu-ZnIn2S4 with water to obtain a dispersion, and filter the dispersion onto the CNTs-PEI membrane obtained in step 3 to obtain a CNTs-PEI / Cu-ZnIn2S4 composite membrane, and the preparation is completed.

2. The method for preparing a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions according to claim 1, characterized in that Step 1: During the heating and acidification of carbon nanotubes CNTs, the volume ratio of concentrated H2SO4 solution to concentrated HNO3 solution is 1-4:1, the mass fraction of concentrated H2SO4 solution is 95-98%, and the mass fraction of concentrated HNO3 solution is 65-70%; the temperature of the heating and acidification treatment is 60-80 °C, and the time is 0.5-2 h.

3. The method for preparing a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions according to claim 1, characterized in that In step 2, the dispersion concentrations of the acidified carbon nanotubes CNTs-COOH and polyethyleneimine PEI in water are 0.05-0.2 g / L and 0.2-2 g / L, respectively; and the ultrasonic dispersion time in step 2 is 0.5-2 h.

4. The method for preparing a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions according to claim 3, characterized in that In step 2, the dispersion concentrations of the acidified carbon nanotubes CNTs-COOH and polyethyleneimine PEI in water are 0.08-0.12 g / L and 0.5-1.0 g / L, respectively.

5. The method for preparing a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions according to claim 1, characterized in that The preparation method of Cu-ZnIn2S4 comprises the following steps: S1: Dissolve zinc salt, indium salt and sulfur source in ultrapure water, adjust the pH value of the mixed solution to acidic, transfer the mixed solution to a hydrothermal reactor, seal the hydrothermal reactor and place it in an oven for reaction; after the reaction is completed, wait for the reactor to cool to room temperature, centrifuge, wash and dry the precipitate to obtain the sulfur-indium-zinc composite material ZnIn2S4; S2: Ultrasonic dispersion of the sulfur-indium-zinc composite material ZnIn2S4 obtained in step S1 in ultrapure water and mixing with a copper salt solution; injecting a reducing solution under magnetic stirring and light irradiation to perform a photodeposition reaction for 5-180 min to obtain Cu-ZnIn2S4.

6. The method for preparing a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions according to claim 5, characterized in that The zinc salt in step S1 is zinc nitrate, zinc sulfate, zinc chloride, zinc phosphate, zinc acetate, zinc citrate, zinc isooctanoate or zinc glycinate, the indium salt is indium nitrate, indium sulfate, indium chloride, indium phosphate, indium acetate or indium citrate, and the sulfur source is thioacetamide, thiourea, ammonium sulfide or sodium thiosulfate; the molar ratio of the zinc salt, indium salt and sulfur source is 2-3:4-6:8-12; the reaction temperature in step S1 is 140-180°C, and the reaction time is 10-20 h.

7. The method for preparing a carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions according to claim 5, characterized in that In step S2, the copper salt is copper nitrate, copper chloride, copper phosphate, copper acetate or ethylenediaminetetraacetic acid copper sodium salt, and the mass ratio of copper to indium zinc sulfide material is 0.1-2:10; The reducing solution in step S2 is an aqueous solution of hydrazine, sodium borohydride, potassium borohydride, ethanol, ammonia water or sodium sulfite, the concentration of the reducing solution is 0.01-0.6 mol / L, the molar ratio of the reducing solution to the copper salt is 3-15:1, and the injection speed of the reducing solution is 2-3 drops per second.

8. A carbon-based self-cleaning membrane material for efficiently separating oil-water emulsions prepared by the method according to any one of claims 1 to 7.

9. Use of the carbon-based self-cleaning membrane material for efficient separation of oil-water emulsion as claimed in claim 8 in membrane separation of oil-water emulsion.

10. The use according to claim 9, characterized in that After the membrane separation is completed, the following regeneration treatment step is also included: after washing with alcohol and water alternately 2-4 times to remove part of the oil component, the membrane is irradiated with visible light.

Citation Information

Patent Citations

  • High-strength self-supporting ultrafiltration membrane prepared through vacuum auxiliary self-assembly and preparation method

    CN105597571A

  • Preparation method of macromolecular modified self-supporting carbon nanotube assembling membrane

    CN106474936A

  • Multiwalled carbon nanotube hybrid ultrafiltration membrane with anti-pollution, self-cleaning and antibacterial properties

    CN107433141A

  • Porous photo-thermal membrane having antibacterial performance and preparation method and application thereof

    CN109265717A

  • Photocatalytic MXene composite membrane and preparation method thereof

    CN114177782A